Morpho-meiotic study in Mentha longifolia from cold desert regions of Lahaul-Spiti and adjoining areas of Himachal Pradesh (India) - Srivastava, Devendra Kumar; Saggoo, Manjit Inder Singh (Acta Biologica Szegediensis, 2019)
A morpho-meiotic study of wild Mentha longifolia (L.) L. (Lamiaceae) is presented from the nine populations (Kukumsari, Zero-point, Kishori, Tosh, Kasol, Key, Tiling, Mudh and Darcha) in and around the cold desert regions of Lahaul-Spiti of Himachal Pradesh. Present work is needful effort to fill the gap of morpho-meiotic (morphological and cytological) knowledge in M. longifolia growing in high altitude regions. Meiotic study revealed the different chromosome counts in these populations as n = 12, n = 12 + 0-3B and n = 9. Presence of B-chromosome in the species is reported for the first time from the study area and it reflects inter-population variation in five important descriptors (such as a nature of whole plant, stem, leaves, inflorescences and pollen) with 17 sub-descriptor states and occurrence of B-chromosomes. Present study reflects the existence of M. longifolia at diploid (2x) level based on base numbers x = 12 and x = 9.